Sustainable reinforced masonry walls under lateral in-plane load: Experimental behavior and code-based predictions. (February 2015) - Clarke, Richard P.
Abstract: Reducing the quantities of materials is an effective means of increasing environmental sustainability. To improve the environmental sustainability of hollow unit reinforced masonry low-rise structures in hurricane or earthquake-prone regions, it is reasonable to use squat walls with horizontal reinforcement in the form of steel mesh. Eight near full-scale walls were tested with control variables as the type and amount of horizontal reinforcement—masonry mesh; fabric reinforcement, and hexagonal wire mesh. Also, the type of masonry unit was 150 mm concrete, 150 mm clay, and 100 mm clay. The walls were tested under in-plane lateral monotonic load to failure and the load–displacement behavior and crack patterns were recorded. The investigation focused on the ultimate load conditions and code-based equations were used to determine theoretical failure loads for comparison with the test failure loads. Given the significance of shear to the response of squat walls, 7 shear strength equations from various codes and other studies were investigated, as well as a failure criterion that considers bending–shear interaction. The performance of the walls was favorable in terms of structural requirements hence can be used for sustainable construction in the manner proposed. Code-based strength equations can be used to design the walls but it is necessary to account for bending–shear interaction. Highlights: We test 8 partially grouted thin squat shear walls with bed joint reinforcement. The proposed conceptual housing design appears technically feasible for sustainable masonry. Code equations over-estimated the strength of the walls if bending–shear interaction is ignored. The MSJC 2008 and the BS 5628 2005 shear strength equations gave the best predictions.